Evaluating and planning information systems in the public sector: The case of Korea. (September 2019) - Cha, Yong Uk; Park, Min Jae
This study proposes a framework for the interim evaluation of, and subsequent planning for, information systems (IS) in the public sector. We incorporate the considerations of cost efficiency and task effectiveness, which are critical for reaping a sustained benefit from IS. We recommend this double-sided analysis as the basis for interim evaluation. We also advise that this framework of evaluation can effectively indicate which subsequent course of action should be taken: maintain the status quo, upgrade functionality, redevelop, or discontinue the IS. We applied this framework to 118 ISs within the South Korean public sector with the k-means clustering method and provided both academic and practical implications.